2021
DOI: 10.1073/pnas.2019285118
|View full text |Cite
|
Sign up to set email alerts
|

T cells selectively filter oscillatory signals on the minutes timescale

Abstract: T cells experience complex temporal patterns of stimulus via receptor–ligand-binding interactions with surrounding cells. From these temporal patterns, T cells are able to pick out antigenic signals while establishing self-tolerance. Although features such as duration of antigen binding have been examined, our understanding of how T cells interpret signals with different frequencies or temporal stimulation patterns is relatively unexplored. We engineered T cells to respond to light as a stimulus by building an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 56 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…This confirms the highly contextual role of eRNAs through the control of transcription burst frequencies, which are known to influence cell-type-specific gene expression profiles (Larsson et al, 2019). Along these lines, a recent study showed that T cells selectively filter oscillatory signals within the minute timescale (O’Donoghue et al, 2021), further supporting the aforementioned model.…”
Section: Introductionsupporting
confidence: 61%
“…This confirms the highly contextual role of eRNAs through the control of transcription burst frequencies, which are known to influence cell-type-specific gene expression profiles (Larsson et al, 2019). Along these lines, a recent study showed that T cells selectively filter oscillatory signals within the minute timescale (O’Donoghue et al, 2021), further supporting the aforementioned model.…”
Section: Introductionsupporting
confidence: 61%
“…Figure 6b) based on either iLID, cpLID (cpLOV2-ssrA and sspB) or CRY2-CIB1 have been developed to conditionally reconstitute a split CAR into a fully functional CAR in the presence of blue light (23,302,303). In the dark, the tumor antigen-sensing unit and/or the effector domains remain separately expressed in two constructs.…”
Section: F Immunomodulationmentioning
confidence: 99%
“…Optogenetics has also been applied to control the activity of therapeutic immune cells, such as the chimeric antigen receptor (CAR) T cells. Optogenetic or light-switchable chimeric antigen receptors (optoCARs or LiCARs; FIGURE 6 B ) based on iLID, cpLID (cpLOV2-ssrA and -sspB), or CRY2-CIB1 have been developed to conditionally reconstitute a split CAR into a fully functional CAR in the presence of blue light ( 23 , 302 , 303 ). In the dark, the tumor antigen-sensing unit and/or the effector domains remain separately expressed in two constructs.…”
Section: Application Of Optogenetics In Physiological Processesmentioning
confidence: 99%
“…systems is inherently limited by the ability to find an altered peptide ligand (APL) that exhibits the desired binding behavior, making questions about specific lengths of pMHC engagement or patterns of binding and rebinding events difficult to answer. To circumvent this issue, several groups have recently developed optogenetic receptor-ligand systems in which binding kinetics are controlled by light patterns [23][24][25][26] (Box 1). While the synthetic nature of optogenetic systems must be considered in interpreting results, these methods enable a new level of precision in dissecting the temporal binding requirements of T cell activation.…”
Section: Manipulation Of T Cell Stimulation Strengthmentioning
confidence: 99%